The Hungarian municipal governments in public accounting - Kovács, Árpád (Public Finance Quarterly, 2024)
Balázs Tóth’s interesting and valuable work entitled “The Hungarian Municipalities in the Public Sector Accounting” was published by Saldo in 2024. There is an extensive literature on how the multi-stakeholder system of the national economy, with its hundreds of thousands of interests, tasks and, not least, values, has become intertwined with the increasingly complex and sophisticated requirements for reporting, accounting and data provision. Accounting, it could be said, is an important chronicler of the functioning of public finances and the related local government system.